Rosa laevigata Attenuates Allergic Asthma Exacerbated by Water-Soluble PM by Downregulating the MAPK Pathway - Ko, Hyun Min; Choi, Seung-Han; Jee, Wona; Lee, Seung-Hyeon; Park, Doil; Jung, Ji Hoon; Lee, Beom-Joon; Kim, Kwan-Il; Jung, Hee-Jae; Jang, Hyeung-Jin (Frontiers in Pharmacology, 2022)
Exposure to water-soluble particulate matter (WPM) containing heavy metals can cause severe inflammatory responses and trigger and exacerbate the onset of asthma. As a follow-up study of Rosa laevigata (RL), this study analyzed the therapeutic effects and mechanisms of oral and intratracheal administration of RL and demonstrated anti-inflammatory effects in asthma models. Worse T-helper cell type 2 (Th2)-related inflammatory and pro-inflammatory responses were observed after simultaneous challenge with ovalbumin (OVA) and WPM. To establish a model of asthma exacerbated by WPM, BALB/c mice were sensitized with OVA+aluminum hydroxide and challenged with OVA+WPM. To confirm the therapeutic efficacy of RL, it was administered both orally and intratracheally. Histopathological analysis of H&E staining confirmed that oral and intratracheal administration of RL alleviated inflammatory cell infiltration in the airways aggravated by OVA+WPM. RL effectively reduced the number of inflammatory cells obtained from the bronchoalveolar lavage fluid. In addition, enzyme-linked immunosorbent assay (ELISA) and multiplex analysis of serum samples confirmed that the administration of RL reduced the levels of immuno-globulin E (IgE), Th2-related cytokines, and pro-inflammatory cytokines. Furthermore, real-time PCR analysis of lung tissue samples confirmed that the release of MUC5AC (Mucin 5AC, Oligomeric Mucus/Gel-Forming) and pro-inflammatory cytokines was reduced by RL, and western blotting confirmed that the administration of RL reduced the phosphorylation of ERK and p38 in the MAPK pathway. In conclusion, oral and intratracheal administration of RL appears to have an anti-asthmatic effect by reducing the secretion of Th2-related cytokines, pro-inflammatory cytokines, and IgE by downregulating the MAPK pathway. Thus, RL has further demonstrated potential for development as an oral and inhaled therapeutic for asthma symptoms exacerbated by WPM exposure.